PERANAN UNDANG-UNDANG NOMOR 25 TAHUN 2007 TENTANG PENANAMAN MODAL - Florentinus Sudiran, Ade Sulistya Ningrum dan (Universitas 17 Agustus 1945 Samarinda, 2018)
This reearh is library one. The problem formulation is how to solvethe conflict of among the sides. The aim of is willing to know how to solvethe disput/conflict of among the sides ? The results f the research can sovebased on.chapter XV, article 32. concerning to solve the conflict are (1)By negotiation to understanding among the sides; (2) If it is not finished itwill be solved by court based on he regulation ; (3) Special for foreigninevestment solution is by arbritage r international court. Sugestion (1) Inthe short term the government has to improve the climate of the businessand investment; (2) The government ha to improve as well as to haveaction for law enforcement.